1980
DOI: 10.1515/hfsg.1980.34.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Degradation of Kraft Lignin in Tetralin

Abstract: WA 98195 and from the U.S. Forest Products Laboratory, Madison, WI 53705 Keywords Kraft lignin Lignin model compounds Hydrocracking Phenols Tetralin Schlüsselwörter (Sachgebiete) Kraftlignin Lignin-Modellverbindungen Hydro-Verkrackung Phenole Tetralin Thermal Degradation of Kraft Lignin in Tetralin SummaryHydrocracking of kraft lignin (Indulin-AT) and of model compounds p-ethylguaiacol and dehydrodihydrodiisoeugenol (DDDI) was studied with tetralin äs hydrogen donor in the temperature ränge 375 to 400° C. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 8 publications
3
75
0
Order By: Relevance
“…Oxidizing routes are generally undesirable due to radical formation which can result in partial repolymerization, whereas hydrogenolysis protocols minimize lignin repolymerization and promote C-O bond cleavage by quenching and recombination of radicals, although the addition of molecular hydrogen can result in fully hydrogenated cyclic hydrocarbons of relatively low commercial value. Hydrogen-donating solvents able to generate/transfer hydrogen have, thus, also shown promise, e.g., Connors et al report hydrogen transfer from ethanol, tetralin, and formic acid during lignin hydrocracking [5], while Kleinert et al reported a novel solvolysis method employing high-pressure thermal treatment of lignin in the presence of ethanol as solvent and formic acid as hydrogen-donor, the latter decomposing to liberate CO 2 and hydrogen [3]. Glycerol [6] and isopropanol [7] are also promising hydrogen-donor solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidizing routes are generally undesirable due to radical formation which can result in partial repolymerization, whereas hydrogenolysis protocols minimize lignin repolymerization and promote C-O bond cleavage by quenching and recombination of radicals, although the addition of molecular hydrogen can result in fully hydrogenated cyclic hydrocarbons of relatively low commercial value. Hydrogen-donating solvents able to generate/transfer hydrogen have, thus, also shown promise, e.g., Connors et al report hydrogen transfer from ethanol, tetralin, and formic acid during lignin hydrocracking [5], while Kleinert et al reported a novel solvolysis method employing high-pressure thermal treatment of lignin in the presence of ethanol as solvent and formic acid as hydrogen-donor, the latter decomposing to liberate CO 2 and hydrogen [3]. Glycerol [6] and isopropanol [7] are also promising hydrogen-donor solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum yield of soluble phenolics was found to be approximately 35% , which compares well with 37% fotmd by Connors et al (1980) from kraft lignin. While the total yields of phenolics from these two studies were similar, the detailed composi tion of the phenolic compotmds showed some differences.…”
Section: Drafi'mentioning
confidence: 52%
“…While the total yields of phenolics from these two studies were similar, the detailed composi tion of the phenolic compotmds showed some differences. High yields of p-methylphenol were reported by Connors et al (1980). Schultz, Preto, Pittman, and Goldstein (1982) In later work, (Inventa 1956b;Giesen 1959), the scale of the process was increased from about the 200 g level up to approximately 10 kg of 1 ignin per run.…”
Section: Drafi'mentioning
confidence: 99%
“…These reductive reaction characteristics of hydrogenolysis tend to reduce or remove functionality in lignin ultimately leading to simpler phenols [2]. Therefore, hydrogenolysis is a promising method for the production of bulk phenolic chemicals from lignin [2,5,142]. A large number of heterogeneous metal-based catalysts (e.g., Ni, Rh, Ni-Mo, Co-Mo and Pd) and a significant smaller number of homogeneous catalysts have been combined with the hydrogenolysis of different lignin models, technical lignins or lignocellulosic biomass [2,141,143].…”
Section: Hydrogenolysismentioning
confidence: 99%